Green solvent-processed, high-performance organic solar cells achieved by outer side-chain selection of selenophene-incorporated Y-series acceptors. Issue 43 (27th October 2021) - Kim, Changkyun; Chen, Shuhao; Park, Jin Su; Kim, Geon-U; Kang, Hyunbum; Lee, Seungjin; Phan, Tan Ngoc-Lan; Kwon, Soon-Ki; Kim, Yun-Hi; Kim, Bumjoon J.
Abstract : We develop a series of green solvent-processable small molecule acceptors (YSe–C3, YSe–C6, and YSe–C9) with different outer side-chains, affording high-performance organic solar cells (16.1%) with green-solvent processing. Abstract : While the power conversion efficiencies (PCEs) of organic solar cells (OSCs) have been dramatically increased through the development of small molecular acceptors (SMAs), achieving eco-friendly solution processability of OSCs is a crucial prerequisite for their practical application. In this study, we develop three new, green solvent-processable SMAs (YSe–C3, YSe–C6, and YSe–C9) with different outer side-chains ( n -propyl (C3), n -hexyl (C6), and n -nonyl (C9)), affording high-performance OSCs with non-halogenated solvent ( o -xylene)-processed active layers. Also, the impact of both outer and inner side-chain engineering of these SMAs on the performance of eco-friendly fabricated OSCs is systematically investigated. The outer side-chain structure has a much more significant impact than the inner side-chain. For example, the PM6:YSe–C6 blend affords high-performance OSCs with a power conversion efficiency (PCE) of over 16%, whereas the PCEs of the YSe–C3- and YSe–C9-based OSCs are only 11–14%. The lower PCEs of PM6:YSe–C3 and C9 are mainly attributed to reduced electron mobility and increased charge recombination, resulting from aggregate-containing non-optimal blend morphologies. Interestingly, the well-optimized morphology of the YSe–C6-based blend also affords OSC devices with active layer thickness-independent PCEs, up to a thickness of >400 nm, demonstrating the great potential for large-area device manufacturing via an eco-friendly printing process. Thus, optimizing the outer side-chain structure of Y-series SMAs is essential for producing green solvent-processed high-performance OSCs.